2014
DOI: 10.1111/tid.12266
|View full text |Cite
|
Sign up to set email alerts
|

Successful hyperbaric oxygen therapy for refractory BK virus‐associated hemorrhagic cystitis after cord blood transplantation

Abstract: BK virus-associated hemorrhagic cystitis (BKV-HC) is a common and major cause of morbidity in recipients of allogeneic hematopoietic stem cell transplantation. A 32-year-old woman developed severe BKV-HC on day 24 after cord blood transplantation (CBT). Despite supportive therapies - such as hyperhydration, forced diuresis, and urinary catheterization - macroscopic hematuria and bladder irritation persisted for over a month. Hyperbaric oxygen (HBO) therapy at 2.1 atmospheres for 90 min per day was started on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…Savva-Bordalo et al reported similar findings with clinical resolution of hematuria in 94% of the 16 patients they treated with HBOT [20]. To date, there continues to be growing evidence of HBOT being an adjunctive therapy for patients with BK virus-associated HC after SCT [14,20,21,27]. Although the primary reason for using HBOT, in this case, was due to persistent HC despite standard of care therapy [20], it is also the third reported case in the United States, to the authors' knowledge, and provides added support as an option for HBOT in these cases.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Savva-Bordalo et al reported similar findings with clinical resolution of hematuria in 94% of the 16 patients they treated with HBOT [20]. To date, there continues to be growing evidence of HBOT being an adjunctive therapy for patients with BK virus-associated HC after SCT [14,20,21,27]. Although the primary reason for using HBOT, in this case, was due to persistent HC despite standard of care therapy [20], it is also the third reported case in the United States, to the authors' knowledge, and provides added support as an option for HBOT in these cases.…”
Section: Discussionmentioning
confidence: 75%
“…Hemorrhagic cystitis is well-reported and documented in the literature as one of the frequent complications of hematopoietic SCT, and it is the result of diffuse inflammation and vascular injury of the bladder mucosa due to immunosuppression and opportunistic infections [16,18]. Late-onset HC is a dangerous and often life-threatening condition that it is frequently associated with reactivation of various viruses such as adenovirus, polyoma, and BKV [14,22]. To further assist in healing, HBOT can be used to treat damaged tissue from hypoxic injury and wound healing through stimulation of angiogenesis and fibroblast proliferation primarily in the HSCT-BKV-HC patient [14,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations